Pengaruh LKPD Berbasis STEM Terintegrasi SDGs Terhadap Critical Thinking Skills Siswa SMP - Zafirah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The low critical thinking skills of junior high school students indicate that science learning is still dominated by a teacher-centered approach and is not yet supported by contextual teaching materials that integrate the STEM approach and sustainability issues. This condition calls for learning innovations that can actively train students' critical thinking skills in a meaningful way that is relevant to the demands of the 21st century. This study aims to examine the influence and improvement of junior high school students' critical thinking skills through the use of STEM-based Student Worksheets (LKPD) integrated with Sustainable Development Goals (SDGs) on the subjects of temperature, heat, and expansion. This study uses a quasi-experimental method with a non-equivalent control group design. The research subjects involved two seventh-grade classes at SMP Negeri 7 Jember, namely the experimental class and the control class, each consisting of 36 students and selected using purposive sampling based on specific criteria. Data were collected through Pretest and Posttest tests compiled based on six indicators of critical thinking skills according to Facione, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. The data were analyzed using normality tests, homogeneity tests, Welch's t-test hypothesis tests, and N-gain tests. The results showed that the use of SDGs-integrated STEM-based LKPD had a significant effect on students' critical thinking skills with a significance value of p < 0.001. The N-gain critical thinking skills score in the experimental class was 0.61, which is in the moderate category, while the control class scored 0.29, which is in the low category. Based on these results, it can be concluded that STEM-based LKPD integrated with SDGs is influential and effective in improving the critical thinking skills of junior high school students and is recommended as innovative teaching material in science learning
FINALISASI oleh Arif 2026 Mei 20
Keywords: critical thinking skills; STEM-based LKPD; Sustainable Development Goals (SDGs); science learning; junior high school students.